The Status Quo of Applying Information and Communication Technology in Teaching at Public Schools According to Itzkan's Stages from Teachers' Point of View in Arramtha Directorate - Mohammad Omari; Haya Al-Daoud (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aims at exploring the realities of the utilization of Information and Communication Technology (ICT) and the readiness and training in teaching according to stages of Itzkan, as perceived by teachers. The population consisted of all the secondary stage teachers at public schools of Arramtha Directorate in Jordan who completed an ICT Program (804 teachers). The sample of the study consisted of 372 teachers who were selected purposefully. The Researchers designed a questionnaire which consisted of 50 items divided into two fields. Results indicated that the level of using tools of ICT according to the stages of Itzkan in teaching amounted to moderate level as follows. The transformation stage ranked first, the substitution stage second, and the transition third with a moderate level of use. Results also revealed that means of the level of readiness and training were moderate, and there was no statistically significant difference at (α=0.05) between the means scores of readiness and training which can be attributed to gender. In addition, there was a statistically significant difference which can be attributed to qualification in favor of MA holders, and experience in favor of ten years or more. In light of the results, the researchers recommended the adoption of the stages of Itzkan in the curricular plan of the Jordanian Ministry of Education to support innovation and creative learning.